Cost Needed to Treat (CNT) and Number Needed to Treat (NNT) analysis of drugs for treatment of heart failure in India. (25th November 2020) - Mullavelil, K; George, V; Thannikkal, A; Aravindakshan, R; John, D; Koshy, C; Venugopal, K
Abstract: Background: Only little attention has been paid to treatment strategies of chronic disease conditions that require long term treatment and repeated hospitalizations Purpose: Our aim was to review cost-effectiveness of guideline directed medical therapy of heart failure in India and identify drugs that can be made available free of cost or at subsidized rates to the patient population. Methods: Data extracted from ten landmark trials in heart failure was used to compute Number Needed to Treat (NNT) and Cost Needed to Treat (CNT) of drugs used in heart failure, to prevent cardiovascular mortality and heart failure re-hospitalization using HDS Plotter- Incremental Cost Effectiveness Calculator. Since various brands (i.e. trade names) with wide cost range are available in Indian market, the average retail price in Indian Rupees for year 2019 was considered and converted to US dollars and used for the analysis.NNT and CNT of each drug was computed and the cost-effectiveness was analyzed. WHO recommendation of three times per capita GDP was used as the cost effectiveness threshold. Results: Medications that were labeled as class I for the treatment of heart failure, were included in our analysis. Ivabradine, Valsartan and Angiotensin Receptor Neprilysin inhibitor (ARNi) did not meet the cost effectiveness criteria for preventing cardio-vascular mortality. For prevention of heart failure re-hospitalization, all drugs except ARNi, met the cost effectiveness threshold. Conclusion: Any future research would need to consider compliance factor along with Willingness to Pay (WTP) to understand the real acceptance of these drugs on the ground in India. Funding Acknowledgement: Type of funding source: None